Taxonomic revision of the monotypic genera of Siculodini (Lepidoptera, Thyridoidea, Thyrididae, Siculodinae) - Queiroz-Santos, Luziany; Casagrande, Mirna Martins; Mielke, Olaf Hermann Hendrik (Zootaxa, 2021)
Four monotypic genera of the tribe Siculodini are revised and adults and their genitalia illustrated for both sexes. Hepialodes Guenée, 1858, Iza Walker, 1865 and Loxiorhiza Warren, 1904 were originally described to include only one species each and they have not been subject to taxonomic revision since that time. From our study, Meskea Grote, 1877, previously with two species, becomes the monobasic Meskea horror Dyar, 1913 syn. nov. of Meskea dyspteraria Grote, 1877. These genera occur in South America, and of these only Meskea extends to the southern North America. Lectotypes are designated for Hepialodes follicula Guenée, 1858, Siculodes nubecula Guenée, 1858 and Zeuzerodes (Siculodes) cervinalis Pagenstecher, 1892.